Direitos humanos na educação: um caminho à cidadania - Abikair, Claudia Maria Gomes Raggi (2009)
This dissertation has the objective of answering the question of why and how the human rights/fundamentals have to be discussed and learned in formal education (elementary school), under an optical dialogical and critical, with a view to emancipation, the redemption of constitutional values, the strengthening of democratic rule of law and citizenship. For this, try to analyze the inconsistency of the constitutional foundations, the instruments guiding the education, ethical principles contained in both the Universal Declaration of Human Rights, as the Federal Constitution of 1988, as well as the National Plan of Education in Human Rights, created by decree No 98, the Special Secretariat for Human Rights, in response to the World Decade for Education on Human Rights. The initiatives of this plan provide referrals for possible light during the formation of the State Committee for Education on Human Rights, bodies established with the purpose of their execution. However, it was concluded that the legal instruments studied have been disregarded on account of the various violations of human rights that is perceived in front of the neoliberal ideology, and that the National Plan for Education on Human Rights emerged as a bridge linking the right to education in this crucial path to citizenship and the democratic rule of law and thus should have its due consideration in view of being placed in a constitutional level.